The Effect of miRNA Gene Regulation on HIV Disease - Chinniah, Romona; Adimulam, Theolan; Nandlal, Louansha; Arumugam, Thilona; Ramsuran, Veron (Frontiers in Genetics, 2022)
Over many years, research on HIV/AIDS has advanced with the introduction of HAART. Despite these advancements, significant gaps remain with respect to aspects in HIV life cycle, with specific attention to virus-host interactions. Investigating virus-host interactions may lead to the implementation of novel therapeutic strategies against HIV/AIDS. Notably, host gene silencing can be facilitated by cellular small non-coding RNAs such as microRNAs paving the way for epigenetic anti-viral therapies. Numerous studies have elucidated the importance of microRNAs in HIV pathogenesis. Some microRNAs can either promote viral infection, while others can be detrimental to viral replication. This is accomplished by targeting the HIV-proviral genome or by regulating host genes required for viral replication and immune responses. In this review, we report on (1) the direct association of microRNAs with HIV infection; (2) the indirect association of known human genetic factors with HIV infection; (3) the regulation of human genes by microRNAs in other diseases that can be explored experimentally to determine their effect on HIV-1 infection; and (4) therapeutic interactions of microRNA against HIV infection.